Innovation Implementation by SMEs in Trinidad and Tobago - Bahaw, Priscilla (European Scientific Journal, ESJ, 2017)
Innovation has become an important contributing factor to firms’ competitive advantage. However, little research has been carried out in understanding innovation in small and medium-sized enterprises in the English-speaking Caribbean countries, particularly in Trinidad and Tobago. This study evaluates the degree to which small and medium-sized enterprises in Trinidad and Tobago engage in innovative activities within their businesses’ operations and identifies the major barriers to innovation that are experienced by these firms. This exploratory study utilized primary data collected through delivery and collection survey questionnaires from 350 randomly selected small and medium-sized enterprises with a minimum active operation period of five years in Trinidad and Tobago. The questionnaire, administered to the longest serving employees of the small and medium-sized enterprises, was designed to collect information on each small and medium-sized enterprise about their innovation experiences, the innovative environment, and innovation barriers. Some of the variables measured were adapted from the Community Innovation Survey found in previous research done by Sileshi Talegeta (2014). The key findings from the research revealed that there are limited efforts of small and medium-sized enterprises in Trinidad and Tobago to implement strategies for encouraging innovation within their organizations. More specifically, it was found that there are low levels of product innovation, process innovation, marketing innovation, and organizational innovation in small and medium-sized enterprises in Trinidad and Tobago. The data suggested that the main barriers to innovation present in small and mediumsized enterprises in descending order of intensity are as follows: organizational culture, lack of reward and recognition, lack of finance, lack of skilled personnel, and lack of knowledge, lack of co-operation, market barriers, and legal barriers. The conclusion from the research findings showed that internal and external factors hindered the small and mediumsized enterprises in Trinidad and Tobago innovation capabilities